ASCOCOTYLE SP. METACERCARIAE (DIGENEA: HETEROPHYIDAE) IN TISSUES OF MULLETS MUGIL LIZAAND MUGIL CUREMA (OSTEICHTHYES: MUGILIDAE) COLLECTED IN THE FISH TRADE OF THE IGUAPE CITY, SAO PAULO, BRAZIL - Kodi Namba, Thales (2012)
The world distribution of oriental culture and the common use of fish which is not cooked manifested problems related to parasites. There is a great incidence of Ascocotyle sp. parasites in mullet fishes, which are part of human culinary spread all over world. The aim of the present study is to estimate the presence of trematode Heterophyidae metacercariae among mullet fishes commercialized at Iguape city Sao Paulo, Brazil. Ascocotyle sp. metacercarie (Digenea: Heterophyidae) were observed and analyzed in viscera and muscles of 60 mullets Mugil liza and 60 mullets Mugil curema (Osteichthyes: Mugilidae) purchased in the fish market of the Iguape city. The extraction of metacercariae of Ascocotyle sp. from viscera and muscles was performed by homogenization in homemade processor. All mullets samples were infected. M. liza and M. curema marketed in city constitute in a potential risk to the population, because of high prevalence of infection (100%) and large numbers of metacercarie in their tissues (up to 939 to M. liza and 92 to M. curema).